2008
DOI: 10.1158/1078-0432.ccr-08-0158
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of 1p32-p36 Is the Most Frequent Genetic Change and Poor Prognostic Marker in Adenoid Cystic Carcinoma of the Salivary Glands

Abstract: Purpose: Adenoid cystic carcinoma (ACC) is a relatively uncommon salivary gland malignancy known for its protean phenotypic features and pernicious clinical behavior. Currently, no effective therapy is available for patients with advanced nonresectable, recurrent, and/or metastatic disease. The purpose of this study is to identify prognostic factors other than tumor stage that can be used to predict the outcome of the patients with ACC. Experimental Design: We used comparative genomic hybridization (CGH) to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 25 publications
7
44
0
1
Order By: Relevance
“…ACC tumors exhibit nonrandom gains or losses of specific chromosome regions, including what may be an ACC‐specific deletion of chromosome 1p35–36. Other frequent deletions are located at 6q24, 12q, and 14q 23, 24, 25. However, the most intriguing alteration is a translocation between chromosomes 6q and 9p [(6;9)(q22–23;p23–24)].…”
Section: Introductionmentioning
confidence: 99%
“…ACC tumors exhibit nonrandom gains or losses of specific chromosome regions, including what may be an ACC‐specific deletion of chromosome 1p35–36. Other frequent deletions are located at 6q24, 12q, and 14q 23, 24, 25. However, the most intriguing alteration is a translocation between chromosomes 6q and 9p [(6;9)(q22–23;p23–24)].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary genetic mechanisms are not well-understood, however. In attempts to identify genomic alterations that occur in ACC, there have been at least 6 studies of ACC cohorts employing the techniques of comparative genomic hybridization (CGH) and array comparative genomic hybridization (aCGH) which globally sample the copy number status of tumor genomes [38][39][40][41][42][43]. The results of these studies have been quite variable but areas of deletion that have been identified in two or more tumors in each of two or more of these studies include 1p (8-44 %), 5q (8-18 %), 6q (14-30 %), 9p (12-33 %), 9q (8-9 %), 12q (9-33 %), 13q (11-35 %), 14q (4-22 %), 17p (11-13 %), and Xp (8-9 %).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of chromosomal ploidy have shown that most classic non-solid ACC show a low degree of aneuploidy, much less than other types of carcinomas, but, ACC with solid histology show increased aneuploidy [51,52]. Studies using CGH and aCGH show a correlation of the degree of genetic alterations (change in DNA copy number, chromosome number, genetic deletion) with the degree of solid growth pattern [39,41,42], consistent with the notion that ACCs with solid histology represent a later stage in tumor progression. One study of four ACC with high-grade transformation suggests that genomic amplification events are more common in transformed tumors than in conventional tumors, with identification of the MYC gene as perhaps a common mechanism for transformation [53].…”
Section: Introductionmentioning
confidence: 99%
“…Further characterization of this molecular alteration in a broad range of head and neck adenoid cystic carcinomas is needed to further define it's role as a potential biomarker. Frequent loss of 1p32-p36 has also been identified in adenoid cystic carcinoma and correlated with solid/basaloid morphology and poorer prognosis [17]. These observations favor potential tumor suppressor genes in this region which are lost and may allow for directed targeted therapy in the future.…”
Section: Mucoepidermoid Carcinomamentioning
confidence: 88%